A spectroscopic survey of biased halos in the reionization Era (ASPIRE): a first look at the rest-frame optical spectra of z > 6.5 quasars using JWST - Yang, Jinyi; Wang, Feige; Fan, Xiaohui; Hennawi, Joseph F.; Barth, Aaron J.; Bañados Torres, Eduardo; Sun, Fengwu; Liu, Weizhe; Cai, Zheng; Jiang, Linhua; Li, Zihao; Onoue, Masafusa; et al. (The astrophysical journal. Part 2, Letters, 2023)
Studies of rest-frame optical emission in quasars at z > 6 have historically been limited by the wavelengths accessible by ground-based telescopes. The James Webb Space Telescope (JWST) now offers the opportunity to probe this emission deep into the reionization epoch. We report the observations of eight quasars at z > 6.5 using the JWST/NIRCam Wide Field Slitless Spectroscopy as a part of the “A SPectroscopic survey of biased halos In the Reionization Era (ASPIRE)” program. Our JWST spectra cover the quasars’ emission between rest frame ∼4100 and 5100 Å. The profiles of these quasars’ broad Hβ emission lines span a full width at half maximum from 3000 to 6000 km s−1. The Hβ-based virial black hole (BH) masses, ranging from 0.6 to 2.1 billion solar masses, are generally consistent with their Mg ii-based BH masses. The new measurements based on the more reliable Hβ tracer thus confirm the existence of a billion solar-mass BHs in the reionization epoch. In the observed [O iii] λ λ 4960,5008 doublets of these luminous quasars, broad components are more common than narrow core components (≤ 1200 km s−1), and only one quasar shows stronger narrow components than broad. Two quasars exhibit significantly broad and blueshifted [O iii] emission, thought to trace galactic-scale outflows, with median velocities of −610 and −1430 km s−1 relative to the [C ii] 158 μm line. All eight quasars show strong optical Fe ii emission and follow the eigenvector 1 relations defined by low-redshift quasars. The entire ASPIRE program will eventually cover 25 quasars and provide a statistical sample for the studies of the BHs and quasar spectral properties.
Gesehen am 28.01.2025